Spectral and shape analysis in medical imaging : first International Workshop, SeSAMI 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 21, 2016, Revised selected papers /: first International Workshop, SeSAMI 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 21, 2016, Revised selected papers. (2016) - Unknown
No abstract available